Evaluation of antioxidant-rich bioactive plant extracts with special reference to Moringa oleifera Lam. for their interference to bacterial quorum sensing and biofilm - Zarrin Haris; Iqbal Ahmad (Elsevier, 2024)
Purpose: Screening of Indian medicinal plants to obtain antioxidant plant extracts for their interference to bacterial quorum sensing and biofilm. Results: The most bioactive fraction of Moringa oleifera leaves extract, i.e., MOEF, has been identified and characterized in this study. In Chromobacterium violaceum 12472, MOEF significantly reduced the amount of violacein produced, i.e.,>70 %. Many virulence factors of Pseudomonas aeruginosa PAO1 were noticeably reduced in the presence of sub-MICs of MOEF. Adding MOEF to the culture media dramatically reduced prodigiosin, protease activity, and swarming of Serratia marcescens. With a >70 % decrease in biofilm development by the test pathogens, MOEF demonstrated broad-spectrum antibiofilm activity. SEM and CLSM examination showed that the biofilm growth on the glass coverslip was significantly decreased. GC/MS detected the major bioactive compounds 2-oleo-palmitostearin, 4-O-methylphorbol-12,13-didecanoate. The most numerous compounds of MOEF were identified using LC-qTOF-MS analysis. Further, the in vivo efficacy of active fraction needs to be assessed to uncover the therapeutic potential of MOEF. Conclusion: The findings of this study revealed that the most antioxidant fraction of M. oleifera, i.e., MOEF, demonstrated anti-infective efficacy in vitro against C. violaceum, P. aeruginosa, and S. marcescens. Concentration-dependent inhibition of Quorum-sensing regulated virulence factors and biofilms highlights its broad-spectrum action. It could be exploited in preparing standardized herbal bioactive products and developing modern phytomedicines. Further, the in vivo efficacy of active fraction needs to be assessed to uncover the therapeutic potential of MOEF.